Особенности проявления сил вязкого трения при движении различных сред и потоков - Перепелица, В.Г.; Шевелев, Г.А. (Доповіді НАН України, 2010)
Наведено результати порiвняльного аналiзу прояву сил в’язкого тертя пiд час руху рiзних середовищ i потокiв, якi дають наочне уявлення про їх рiзноманiття, включаючи граничнi умови, режими i схеми течiї. Такий повний аналiз виконано вперше. We have performed, for the first time, the complete comparative analysis of manifestations of the forces of viscous friction during the motion of various media and flows which gives a clear representation of their diversity, including the boundary conditions, modes, and schemes of currents.